Analisis Kondisi Awal Pembelajaran Fisika SMAN Kota Padang (Dalam Rangka Pengembangan Bahan Ajar Fisika Multimedia Interaktif Berbantuan Game) - Djusmaini Djamas; Ramli Ramli; Silvi Yulia Sari; Rio Anshari (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2016)
Abstract Low understanding of the students in learning physics suspected because physics learning patterns have not been able to optimize students' critical thinking skills. As known, the critical thinking is the key to academic success of a student. Currently, lack of critical thinking skills of students as one of the clear indicators of low quality of education. If this is allowed, then the physics learning outcomes in the future will be very apprehensive. Therefore, efforts should be made to improve critical thinking skills using interactive multimedia teaching materials based on discovery learning aided games. The development of teaching materials are using ADDIE Model. The first step of this model is analysis, i.e. preliminary study of physics learning how to condition that has lasted until today. Based on the analysis of the field findings, will be designed Interactive Multimedia Instructional Materials, and then will be the development of Instructional Materials. In this paper, we will present the results of the initial needs analysis to develop the interactive multimedia teaching materials based on discovery learning aids game for physics learning in the future. Keywords: Critical Thinking, Discovery Learning, Game, Interactive Multimedia, Physics Learning